Role of robotics as a key platform for digital advancements in surgery - Backer, Pieter De; Nickel, Felix (The British journal of surgery, 2024)
Throughout the last two centuries, surgery has encountered four major revolutions. The first revolution started with anatomical mastery, asepsis and anaesthesia and thereafter, progression towards complex multi-organ surgeries, organ transplants and prosthetics occurred. In recent decades, video-assisted minimally invasive surgery and robotic surgery have reduced invasiveness and arguably increased the precision of surgical procedures. Currently we stand at the edge of the era of digital surgery, which involves the incorporation of cutting-edge technologies like extended reality (incorporating virtual reality, augmented reality and mixed reality), telepresence and artificial intelligence (AI) to enhance surgical training, precision, efficiency and outcome1. This fourth revolution is based on availability of computational resources, democratization of information and connectivity with high-bandwidth internet in combination with increased access to data centres offering data storage, centralization and processing. A digitized world with nearly unrestrained data access and computing power enables new research avenues aiming to optimize surgical performance and enhance patient care and recovery. The concept of Surgical Data Science uses all available local patient data from electronic health records, intra- and perioperative sensor data combined with globally available data and evidence to improve treatment efficacy and safety.
Gesehen am 19.06.2024